Effect of different beneficial insect pollinators on fruit setting of litchi - Hossen, M A; Haque, M E; Ahmed, M T; Hasan, S A M G (Bangladesh Journal of Nuclear Agriculture, 2025)
An experiment was carried out at the BAU Germplasm Centre (GPC), Bangladesh Agricultural University, Mymensingh during February to May, 2021 to study the effect of beneficial insects on litchi flower pollination and fruit setting. The experiment was laid out in a Randomized Complete Block Design with three replications of four litchi varieties viz. Mongolbari, China-3, Bombai, Mozzafforpuri. In each replication same number of blooming flower was considered for the study. The data were recorded on the number of flower per inflorescence, beneficial insects per inflorescence, fruit set per inflorescence and fruit dropping record. It was found that most of the beneficial insects were hymenopteran and dipteran insects which covered 89 percent of total beneficial insects. Honey bee and syrphid fly were found as better pollinator. In this experiment maximum number of fruit set per inflorescence was found in the Bombai variety, where the highest number of beneficial insects (2.49) per variety was found. On the other hand, lowest number of beneficial insects (1.37) and lowest fruit set was found in China-3 variety (6.33) where harmful insects were higher (1.72). After pollination when fruit set was at marble stage, number of fruit set and fruit dropping per inflorescence was recorded. So, it can be concluded that beneficial insects as pollinators play a direct role in litchi flower pollination and fruit set. It could be concluded that timely establishment of colonies in sufficient number and conservation of the pollinators in litchi orchard is essential to ensure better pollination and fruit set of litchi. Bangladesh J. Nuclear Agric, 38(2): 89-96, 2024